Community Health Centers as Arenas of Public Health Policy Implementation and Social Practice: A Systematic Review - Afgani, Nurham Al; Sulistyawati, Sulistyawati; Rosyidah, Rosyidah (Reflection Journal, 2026)
Community Health Centers, known in Indonesia as Puskesmas, hold a strategic position in the national health system as primary health care facilities and local sites of public health policy implementation. However, most studies on Puskesmas have focused on technical, managerial, and service performance aspects, while limited attention has been given to how health policies are interpreted, negotiated, and adapted through everyday social practices. This systematic review aims to analyze the role of Puskesmas as arenas of public health policy implementation and social practice. The review followed the PRISMA guidelines and searched articles published between 2015 and 2025 through Google Scholar, PubMed, and Garuda. Articles were selected based on their relevance to primary health care, policy implementation, and social practice. Six articles met the inclusion criteria and were analyzed using thematic synthesis. The findings show that Puskesmas function as spaces where national health policies are translated into local practice, particularly in the implementation of the National Health Insurance/BPJS and the Healthy Indonesia Program with a Family Approach. Policy implementation is shaped by human resource capacity, infrastructure, intersectoral coordination, health literacy, local culture, and community participation. This review confirms that strengthening Puskesmas requires a contextual, adaptive, participatory, and socially sensitive policy approach that recognizes Indonesia’s diverse geographical and sociocultural conditions